2007
DOI: 10.1111/j.1574-6941.2007.00337.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of arbuscular mycorrhizal mycelial exudates on soil bacterial growth and community structure

Abstract: Plant root systems colonized by arbuscular mycorrhizal (AM) fungi have previously been shown to influence soil bacterial populations; however, the direct influence of the AM extraradical mycelium itself on bacterial growth and community composition is not well understood. In this study, we investigated the effects of exudates produced by AM extraradical mycelia on the growth and development of an extracted soil bacterial community in vitro. The chemical composition of the mycelial exudates was analysed using p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
189
0
8

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 358 publications
(215 citation statements)
references
References 24 publications
4
189
0
8
Order By: Relevance
“…3). This clustering was primarily based on the utilization of 15 of 18 com-pounds, which have previously been postulated to be often present in fungal exudates (28), in the Biolog assay (14,21,24,25,31). The compounds utilized by B. terrae (BS001) were L-arabinose, D-arabitol, ␣-D-glucose, M-inositol, D-mannitol, D-trehalose, citric acid, D-alanine, L-aspartic acid, L-glutamic acid, L-phenylalanine, L-proline, D-serine, L-threonine, and glycerol.…”
Section: Resultsmentioning
confidence: 99%
“…3). This clustering was primarily based on the utilization of 15 of 18 com-pounds, which have previously been postulated to be often present in fungal exudates (28), in the Biolog assay (14,21,24,25,31). The compounds utilized by B. terrae (BS001) were L-arabinose, D-arabitol, ␣-D-glucose, M-inositol, D-mannitol, D-trehalose, citric acid, D-alanine, L-aspartic acid, L-glutamic acid, L-phenylalanine, L-proline, D-serine, L-threonine, and glycerol.…”
Section: Resultsmentioning
confidence: 99%
“…As the communities that remained in solution were also different between compartments containing hyphae or glass wool, it is not unlikely that hyphal exudates have had a role in shaping these communities. A study by Toljander et al (2007), using exudates isolated from AMF hyphae, have also shown a marked influence of AMF hyphal exudates on bacterial community composition. They detected several low-molecular-mass sugars and organic acids as well as some unidentified high-molecularmass compounds in hyphal exudates.…”
Section: Discussionmentioning
confidence: 99%
“…Like plant roots, also AMF hyphae produce exudates and these exudates might explain the observed differences in soil bacterial communities. It has been found that extracted AMF hyphal exudates can stimulate bacterial growth (Filion et al, 1999) and change the bacterial community composition (Toljander et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Sood (2003) proved a stronger attraction of Azotobacter chrococcum and P. fluorescens by exudates collected from tomato roots colonized by G. fasciculatum than by exudates collected from non-colonized roots. Recently, a bacterial community extracted from soil was shown to be signif icantly affected after 48 h when inoculated with exudates produced by AM mycelia in comparison to a control composed of culture medium (Toljander et al, 2007). Nonetheless, in soil, reduction in exudation through defoliation of pea plants did not modify the PCR-DGGE profile of rhizosphere bacteria, whereas missing and additional bands where observed from the rhizosphere of plants precolonized with G. intraradices (Vestergård et al, 2008).…”
Section: Mechanisms Of Interactions Between Amb and Am Extraradical Nmentioning
confidence: 97%